ANALISIS GAP PELAYANAN PERIZINAN DI MAL PELAYANAN PUBLIK KABUPATEN SEMARANG - Nurbaliza Istian, An Nafia; Zarkasyi Rahman, Amni; Rina Herawati, Augustin (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Public services provided by the Semarang Regency One-Stop Investment and Integrated Services Office can meet the needs of the community, so it is necessary to have good and maximum service quality, because quality is a form of totality of the characteristics of a product or service that supports the ability to meet needs. Although it can meet the needs of the community, there is still a gap between what has been provided in the service at the Semarang Regency One-Stop Investment and Integrated Service Office and what is received by the community. This research will be conducted using a qualitative research method with a descriptive approach. Based on the findings of service gaps that occur in licensing services, it shows that the quality of licensing services at the Semarang Regency Public Service Mall is not yet fully categorized as good. To overcome the various gaps that occur in licensing services at the Semarang Regency Public Service Mall, it is important for the licensing service government to better understand the perspective and expectations of the community, and make efforts to improve communication, transparency, and responsiveness in services.